2004
DOI: 10.1007/s00467-004-1512-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant enzymes in children with chronic renal failure

Abstract: Increased lipid peroxidation (LP) has been observed in dialysis patients and in predialysis adults with advanced chronic renal failure (CRF). The aim of this study was to investigate whether predialysis CRF children have increased LP in plasma and red blood cells (RBC) and to evaluate the activity of the antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)] in RBC. Concentrations of selenium (Se), copper (Cu), and zinc (Zn)-cofactors of these enzymes-were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…The increased levels of ascorbic acid and ceruloplasmin found in this study indicate intact oxidant defense mechanism, as they can act as freeradical scavengers [18]. Zwołińska et al [19] observed significantly raised levels of plasma and erythrocyte MDA and reduced zinc, copper, and selenium concentrations in patients with chronic renal failure in predialysis phase when compared with controls. The authors concluded that increased lipid peroxidation and decreased antioxidant capacity is also found in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 82%
“…The increased levels of ascorbic acid and ceruloplasmin found in this study indicate intact oxidant defense mechanism, as they can act as freeradical scavengers [18]. Zwołińska et al [19] observed significantly raised levels of plasma and erythrocyte MDA and reduced zinc, copper, and selenium concentrations in patients with chronic renal failure in predialysis phase when compared with controls. The authors concluded that increased lipid peroxidation and decreased antioxidant capacity is also found in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 82%
“…In detail, the in vitro experiment has proven that oxidative stress stimulates vascular smooth muscle cells to produce Hsp90-␣ [28] . ROS overactivity, present in both APD and HD patients, could, therefore, at least partially explain the origin of increased Hsp90-␣ [29][30][31] , especially when the fact that the Hsp90-␣ expression on mesothelial cells from the peritoneal dialysis subjects does not respond to the exposure to peritoneal fluid is taken into account [32] . This finding may support the hypothesis that, at least in the peritoneal dialysis patients, Hsp90-␣ elevation does not depend on the type of renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Noteworthy, in this regard is the fact that oxidative stress is also considered to be the final common pathway for the development of diabetic complications including nephropathy and hence can become an important confounding variable because diabetes mellitus (DM) has been implicated as the single largest cause of CKD. 3,4 Several factors are responsible for the regulation of the balance between pro-oxidants and antioxidants in the body.…”
Section: Introductionmentioning
confidence: 99%